ANALISIS YURIDIS TERHADAP KEDUDUKAN KECERDASAN BUATAN ATAU ARTIFICIAL INTELLIGENCE SEBAGAI SUBJEK HUKUM PADA HUKUM POSITIF INDONESIA - Febri Jaya; Wilton Goh (Universitas Islam Syekh Yusuf, 2021)
Indonesia need policies and regulations which can adapt with current technological development especially Artificial Intelligence. The more sophisticated, Artificial Intelligence capability and continuously development over time, Artificial Intelligence cannot be acknowlegde as a legal object but Artificial Intelligence can be acknowledge as a legal subject, so the big challenge for government is prepare policies and regulations for Artificial Intelligence which will become a part of social life on Indonesia Positivisme Law for achieve people’s welfare and prosperity in the development of the state from suggestion, consideration and knowledge which can be conveyed to law enforcers especially on Artificial Intelligence. This research uses normative law juridical research methods. The legal position of Artificial Intelligence can be applied to the special laws of Artificial Intelligence as a legal subject, which is same as corporation. In order to have clearer legal certainty regarding the responsibility for legal acts commited by Artificial Intelligence, the identity of Artificial Intelligence can be made of an authentic deed.